Preparation method of high oleic acid peanut oil with original flavor
By forming a starch composite liquid network structure and low-temperature treatment technology on the surface of peanut particles, the problem of oleic acid loss during peanut oil drying is solved, and peanut oil preparation with high oleic acid content and high oil yield is achieved, which improves the retention rate of oleic acid and oil quality.
Patent Information
- Application Number
- CN202411066083.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2024-12-13
AI Technical Summary
During the drying process of peanut oil, oleic acid is easily affected by heat and oxygen, resulting in high-temperature oxidation and decomposition, affecting the content and quality of oleic acid, and the existing drying methods are costly or inefficient.
The starch composite liquid is used to form a network structure on the surface of peanut particles, combined with infrared drying and low-temperature pressing filtration technology, to block oleic acid from contact with the outside world, reduce oxidation and thermal decomposition, and improve the extraction efficiency of oleic acid.
The preparation of peanut oil with high oleic acid content is achieved, which reduces the oxidation and thermal decomposition losses of oleic acid, improves the oil yield and oleic acid retention rate, and ensures the quality and economicality of peanut oil.
Smart Images

Figure BDA0004979383180000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of deep processing of food, and more specifically, to a method for preparing high-oleic peanut oil with original aroma and flavor. Background Art
[0002] Peanut oil is an edible oil with a clear color, rich aroma, and is easy to digest. Peanut oil contains about 80% unsaturated fatty acids, including about 41% oleic acid and about 38% linoleic acid, which can help lower blood cholesterol and triglycerides and reduce the risk of cardiovascular disease. In addition, unsaturated fatty acids can also enhance the permeability of cell membranes, aid in the absorption of nutrients and the excretion of waste, and are beneficial to physical health.
[0003] However, the oleic acid content of peanut oil is easily affected by heat and oxygen. In the preparation process of peanut oil, it is generally necessary to dry the peanuts to remove moisture. However, if the temperature is high during the drying process, although the drying effect is better, it is easy to cause high-temperature oxidation and decomposition of oleic acid. If the drying temperature is low, not only the drying time is long, but the moisture is also easy to be not dried thoroughly, thus affecting the quality of the peanut oil; vacuum drying has a high cost.
[0004] Therefore, how to prepare a peanut oil with high oleic acid content is a problem to be solved. Summary of the invention
[0005] In order to prepare a peanut oil with high oleic acid content, the present application provides a method for preparing high oleic peanut oil with original flavor.
[0006] The present application provides a method for preparing high oleic peanut oil with original aroma and flavor, which adopts the following technical scheme: A method for preparing high-oleic peanut oil with original flavor comprises the following steps: S1. Peanuts are selected, mold removed, and red skin removed to obtain peanut kernels; S2, soaking the peanuts in the starch composite liquid for 1-2 minutes, then taking out the peanuts and draining off the excess liquid on the surface to obtain liquid-coated peanuts, and drying and post-treating the liquid-coated peanuts to obtain coated peanuts; S3, the coated peanuts are first dried at 80-100°C for 1-3 minutes, and then irradiated and dried with infrared rays at 60-65°C for 30-40 minutes to obtain dry peanuts; S4. The dried peanut kernels are pressed and filtered at low temperature to obtain finished peanut oil.
[0007] By adopting the above technical scheme, the red skin of peanut kernels is removed, which is convenient for drying and oil outflow; the peanut kernels are soaked in starch composite liquid for a limited time, so that the starch composite liquid forms a thin layer on the surface of the peanut kernels, and as the post-drying treatment proceeds, the starch composite liquid forms a breathable network structure attached to the surface of the peanut kernels. On the one hand, the network structure can block the direct contact of oleic acid substances with the outside world and reduce the separation of oleic acid in peanuts; on the other hand, the generation of the network structure can generate a barrier structure between the peanut kernels during the peanut kernel oil extraction process, so as to avoid the peanut kernels from sticking to each other due to oil and blocking each other's oil outflow path, thereby ensuring that the oleic acid in the peanuts is extracted together in the peanut oil, so that the peanut oil contains a higher content of oleic acid.
[0008] During the drying process, the coated peanuts are first dried briefly at 80-100°C to quickly remove moisture from the surface of the peanuts. Then, the better penetration and uniform irradiation effects of infrared rays are used to promote the removal of moisture from the inside of the peanuts and ensure the uniformity of moisture removal. By limiting the infrared temperature and drying time, the dry peanuts are evenly dried, reducing the thermal decomposition loss of oleic acid. Low-temperature pressing and low-temperature filtration are used to further reduce the loss of oleic acid.
[0009] The network structure formed by the starch composite liquid blocks the direct contact between the oleic acid in the peanuts and the external environment, thereby reducing the oleic acid oxidation loss. The thermal decomposition loss of the oleic acid is reduced through low-temperature drying, low-temperature pressing, and low-temperature filtration treatments, thereby ensuring that the oleic acid in the peanuts is efficiently extracted into the peanut oil, and a high-oleic peanut oil is obtained.
[0010] Preferably, the starch composite liquid is made of starch gelatinized liquid, hydroxyapatite nanowires, high acyl gellan gum solution and glycerol in a mass ratio of 100:1-2:20-30:2-6.
[0011] By adopting the above technical scheme, starch gelatinized liquid, hydroxyapatite nanowires, and high acyl gellan gum solution are matched, and under the plasticizing effect of glycerol, the starch composite liquid can form a cross-linked network structure on the surface of peanut grains, and the network structure is not only porous, but also intertwined and folded; the porous structure is convenient for multi-directional refraction of infrared rays, thereby ensuring the uniform drying effect of the peanut grains, and the intertwined and folded network can block oleic acid from direct contact with the external environment as much as possible, thereby preventing oleic acid from being oxidized as much as possible; at the same time, the high acyl gellan gum in the network structure has good flexibility, and the hydroxyapatite nanowires can also support the network structure. During the pressing process, it can block adjacent peanut grains from being bonded together due to oil as much as possible. Starch, high acyl gellan gum and hydroxyapatite nanowires are insoluble in oil and are not easy to produce adhesion in an oil environment. Therefore, the network structure can provide an outflow channel for oil and prevent peanut grains from sticking to ensure the oil yield of peanuts, so that the peanut oil has a high oil yield and a high oleic acid content.
[0012] Preferably, the starch gelatinized liquid is prepared by the following method: Weigh starch, add water and stir evenly, then heat and gelatinize to obtain starch liquid; add calcium caseinate to the starch liquid at a mass ratio of 1:0.05-0.1, mix and stir evenly to obtain starch gelatinized liquid.
[0013] By adopting the above technical scheme, starch liquid and calcium caseinate are matched, and the calcium ions in calcium caseinate are used to match with the high acyl gellan gum solution to improve the cross-linking structure stability of the high acyl gellan gum solution, thereby ensuring the formation of a network structure. When the oil in the peanuts flows out, the oil and oleic acid in the oil can flow out of the peanut cake through the pores of the network structure formed by starch, calcium caseinate and the high acyl gellan gum solution, thereby ensuring that the oil in the peanuts is efficiently extracted, so that the peanut oil has a higher oil yield and a higher oleic acid content.
[0014] Preferably, the hydroxyapatite nanowires are prepared by the following method: A sodium carboxymethyl cellulose solution is evenly sprayed on the hydroxyapatite nanowire filaments at a mass ratio of 1:0.1-0.2, and then tetrapod-shaped zinc oxide whiskers are added, the mass ratio of the hydroxyapatite nanowire filaments to the tetrapod-shaped zinc oxide whiskers is 1:0.1-0.3, and the finished product is obtained after drying and dispersion.
[0015] By adopting the above technical scheme, the viscosity of the sodium carboxymethyl cellulose solution is utilized on the hydroxyapatite nanowire to adhere the four-needle zinc oxide whiskers to the surface of the hydroxyapatite nanowire. During the pressing process, the four-needle zinc oxide whiskers on the surface of the hydroxyapatite nanowire in contact with the peanut kernel can penetrate into the peanut kernel, thereby increasing the oil extraction rate and oil extraction rate of the peanut kernel, providing a flow path for the oil in the peanut, making it easier to collect the oil extracted from the peanut, and making the peanut oil have a high oil extraction rate and high oil extraction rate.
[0016] Preferably, the average length of the hydroxyapatite nanowire filaments is 200-600 μm.
[0017] By adopting the above technical scheme, the length of the hydroxyapatite nanowire filaments is limited, and by utilizing their good flexibility, they not only play a supporting role in the network structure but also have a certain flexibility, which facilitates the starch composite liquid to form an interwoven folded network structure; during the pressing process, the interwoven folded network structure can block adjacent peanut grains, making it difficult for adjacent peanut grains to adhere to each other due to oil, so that the peanut oil has a higher oil yield; and the adhesion effect of the hydroxyapatite nanowire filaments on the surface of the peanut grains can further control the direct contact between oleic acid and the external environment, and control the oxidation of oleic acid, thereby ensuring that the peanut oil has the advantage of high oleic acid.
[0018] Preferably, the high acyl gellan gum solution is prepared by the following method: Weigh high acyl gellan gum, place it in water and stir, heat it to 85-90° C. and stir until it is completely dissolved to obtain a dissolving solution, then mix the dissolving solution and PMMA microspheres at a mass ratio of 100:1-5 to obtain a finished product.
[0019] By adopting the above technical scheme, PMMA microspheres are added to high acyl gellan gum, and the better infrared projection effect of PMMA microspheres is utilized to facilitate infrared rays to penetrate the film layer formed by high acyl gellan gum. In combination with the gaps in the network structure and the refraction effect of infrared rays, infrared rays are evenly irradiated on the surface of peanut grains, thereby achieving uniform drying and reducing the contact rate between oleic acid in peanuts and external oxygen, thereby controlling the oxidation of oleic acid and making peanut oil have the advantage of high oleic acid.
[0020] Preferably, the post-processing steps are as follows: Spray vitamin E evenly on the surface of the liquid-coated peanuts at a mass ratio of 100:1-2, and then air-dry.
[0021] By adopting the above technical scheme, when vitamin E is on the surface of the liquid-coated peanut grains, it can reduce the oxidation of oleic acid in the peanut grains by external oxygen; when the peanut grains are extracted for oil, vitamin E, as a fat-soluble antioxidant, can gradually dissolve in the oil and enter the peanut oil, further controlling the oleic acid in the peanut oil from being easily oxidized during the filtering and storage process, so that the peanut oil has a higher oleic acid content.
[0022] Preferably, the selection is to select peanuts whose oleic acid content accounts for 75-80% of the total fatty acid content.
[0023] By adopting the above technical scheme, the peanut oil prepared from peanuts with high oleic acid content has the advantage of high oleic acid.
[0024] Preferably, the specific steps of low temperature pressing are as follows: First, press at a temperature of 45-50°C and a pressure of 35-40MPa for 1-1.5h; then press at a temperature of 50-55°C and a pressure of 45-50MPa for 1.5-2.5h.
[0025] By adopting the above technical scheme, the peanut oil is first pressed at a temperature of 45-50°C and a pressure of 35-40MPa to extract most of the oil in the peanut oil, and then the temperature and pressure are increased to ensure that the residual oil in the peanut oil is extracted, so that the peanuts have a higher oil yield, and the pressing temperature is low, which can make oleic acid less likely to be thermally oxidized and thermally decomposed, so that the peanut oil has the advantage of a high oleic acid content.
[0026] Preferably, the temperature of the low temperature filtration is 40-45°C.
[0027] By adopting the above technical solution, the problem of low-temperature filtration is limited and the oleic acid content in the peanut oil is not easily affected.
[0028] In summary, this application has the following beneficial effects: 1. The network structure formed by the starch composite liquid blocks the direct contact between the oleic acid in the peanuts and the external environment, thereby reducing the oleic acid oxidation loss. Through low-temperature drying, low-temperature pressing, and low-temperature filtration, the thermal decomposition loss of oleic acid is reduced, thereby ensuring that the oleic acid in the peanuts is efficiently extracted into the peanut oil, and a high-oleic peanut oil is obtained.
[0029] 2. Although the network structure on the surface of peanut grains cannot completely isolate external oxygen like waxy substances, the interwoven network structure can still block some oxygen, and combined with the antioxidant effect of vitamin E, it further prevents oleic acid from being oxidized. After the peanuts are oxidized, oxides or peroxides will be produced, which are no longer the original oleic acid substance, affecting the quality of the peanut oil. DETAILED DESCRIPTION
[0030] The present application is further described in detail below with reference to the embodiments.
[0031] The following raw materials are all commercially available.
[0032] Preparation example of starch composite liquid Preparation Example 1: The starch composite liquid is prepared by the following method: Weigh starch, add water and stir evenly, heat to 80°C, the starch is corn starch, stir until completely gelatinized, and obtain a starch solution with a mass fraction of 3%; add 0.08kg of calcium caseinate to 1kg of starch solution, stir at a speed of 200r / min for 20min, and obtain a starch gelatinized solution after mixing evenly; 0.15 kg of sodium carboxymethyl cellulose solution is uniformly sprayed on 1 kg of hydroxyapatite nanowire filaments, wherein the average length of the hydroxyapatite nanowires is 500 μm, the average diameter is 20 nm, and the sodium carboxymethyl cellulose solution is a 1% sodium carboxymethyl cellulose aqueous solution by mass; then 0.2 kg of tetrapod-shaped zinc oxide whiskers are added, wherein the average length of the tetrapod-shaped zinc oxide whiskers is 80 μm, and the mixture is dried and dispersed until the hydroxyapatite nanowire filaments do not stick to each other and agglomerate, thereby obtaining hydroxyapatite nanowires; Weigh high acyl gellan gum, place it in water and stir, heat it to 85°C and stir until it is completely dissolved, to obtain a 2% by mass solution, then mix 100 kg of the solution and 3 kg of PMMA microspheres, the average particle size of the PMMA microspheres is 20 μm, to obtain a high acyl gellan gum solution; 100 kg of starch gelatinized liquid, 1.5 kg of hydroxyapatite nanowires, and 25 kg of high acyl gellan gum solution were weighed and mixed and stirred evenly, and then 5 kg of glycerol was added and continued to be stirred evenly, and vacuum degassing was performed to obtain a starch composite liquid.
[0033] Preparation Example 2: This preparation example differs from Preparation Example 1 in that: Weigh starch, add water and stir evenly, heat to 80°C, the starch is corn starch, stir until completely gelatinized, and obtain a starch liquid with a mass fraction of 3%; add 0.05kg of calcium caseinate to 1kg of starch liquid, stir at a speed of 200r / min for 20min, and obtain a starch gelatinized liquid after mixing evenly; 0.1 kg of sodium carboxymethyl cellulose solution is uniformly sprayed on 1 kg of hydroxyapatite nanowire filaments, the average length of the hydroxyapatite nanowires is 200 μm, and the sodium carboxymethyl cellulose solution is a 1% sodium carboxymethyl cellulose aqueous solution by mass; then 0.1 kg of tetrapod-shaped zinc oxide whiskers are added, the average length of the tetrapod-shaped zinc oxide whiskers is 80 μm, and the mixture is dried and dispersed until the hydroxyapatite nanowire filaments do not stick to each other and agglomerate, thereby obtaining hydroxyapatite nanowires; Weigh high acyl gellan gum, place it in water and stir, heat it to 85° C. and stir until it is completely dissolved to obtain a 2% by mass solution, then mix 100 kg of the solution and 1 kg of PMMA microspheres to obtain a high acyl gellan gum solution; 100 kg of starch gelatinized liquid, 1 kg of hydroxyapatite nanowires, and 20 kg of high acyl gellan gum solution were weighed and mixed and stirred evenly, and then 2 kg of glycerol was added and continued to be stirred evenly, and vacuum degassing was performed to obtain a starch composite liquid.
[0034] Preparation Example 3: This preparation example differs from Preparation Example 1 in that: Weigh starch, add water and stir evenly, heat to 80°C, the starch is corn starch, stir until completely gelatinized, and obtain a starch liquid with a mass fraction of 3%; add 0.1kg of calcium caseinate to 1kg of starch liquid, stir at a speed of 200r / min for 20min, and obtain a starch gelatinized liquid after mixing evenly; 0.2 kg of sodium carboxymethyl cellulose solution was uniformly sprayed on 1 kg of hydroxyapatite nanowire filaments, the average length of the hydroxyapatite nanowires was 600 μm, and the sodium carboxymethyl cellulose solution was a 1% sodium carboxymethyl cellulose aqueous solution by mass; then 0.3 kg of tetrapod-shaped zinc oxide whiskers was added, the average length of the tetrapod-shaped zinc oxide whiskers was 80 μm, and the mixture was dried and dispersed until the hydroxyapatite nanowire filaments did not stick to each other and agglomerated, thereby obtaining hydroxyapatite nanowires; Weigh high acyl gellan gum, place it in water and stir, heat it to 90° C. and stir until it is completely dissolved to obtain a 2% by mass solution, then mix 100 kg of the solution and 5 kg of PMMA microspheres to obtain a high acyl gellan gum solution; 100 kg of starch gelatinized liquid, 2 kg of hydroxyapatite nanowires, and 30 kg of high acyl gellan gum solution were weighed and mixed and stirred evenly, and then 6 kg of glycerol was added and continued to be stirred evenly, and vacuum degassing was performed to obtain a starch composite liquid. Example
[0035] Embodiment 1: A method for preparing high oleic peanut oil with original flavor: S1. Peanuts are selected to select peanuts with oleic acid content accounting for 78-80% of the total fatty acid content, and moldy peanuts are removed. Then, peanuts are placed in a peanut peeling machine to remove the red skin by mechanical friction to obtain peanut kernels; S2, soaking 10 kg of peanuts in 50 kg of the starch composite liquid prepared in Preparation Example 1 for 1 min, then taking out the peanuts and draining off excess liquid on the surface to obtain liquid-coated peanuts; spraying 2 kg of vitamin E evenly on the surface of 100 kg of liquid-coated peanuts, where the average particle size of the vitamin E is 40 μm; then air-drying the starch composite liquid to form a thin layer with an average thickness of 1 mm, to obtain coated peanuts; S3, drying the coated peanuts at 90°C for 2 minutes, and then drying them at 60°C for 35 minutes using infrared rays to obtain dry peanuts; S4. The dry peanut kernels are pressed at a temperature of 48°C and a pressure of 38 MPa for 1.2 h, then at a temperature of 52°C and a pressure of 48 MPa for 2 h, and finally filtered at a temperature of 45°C to obtain finished peanut oil.
[0036] Embodiment 2: This embodiment differs from Embodiment 1 in that: S1. Peanuts are selected to select peanuts with oleic acid content accounting for 75-78% of the total fatty acid content, and moldy peanuts are removed. Then, peanuts are placed in a peanut peeling machine to remove the red skin by mechanical friction to obtain peanut kernels; S2, soaking 10 kg of peanuts in 50 kg of the starch composite liquid prepared in Preparation Example 2 for 1 min, then taking out the peanuts and draining off excess liquid on the surface to obtain liquid-coated peanuts; spraying 1 kg of vitamin E evenly on the surface of 100 kg of liquid-coated peanuts, and then air-drying them to obtain coated peanuts; S3, the coated peanuts are first dried at 80°C for 3 minutes, and then dried at 60°C for 40 minutes using infrared rays to obtain dry peanuts; S4. The dry peanut kernels are pressed at a temperature of 45°C and a pressure of 35 MPa for 1.5 h, then at a temperature of 50°C and a pressure of 45 MPa for 2.5 h, and finally filtered at a temperature of 40°C to obtain finished peanut oil.
[0037] Embodiment 3: This embodiment differs from Embodiment 1 in that: S2, soaking 10 kg of peanuts in 50 kg of the starch composite liquid prepared in Preparation Example 3 for 2 min, then taking out the peanuts and draining off excess liquid on the surface to obtain liquid-coated peanuts; spraying 2 kg of vitamin E evenly on the surface of 100 kg of liquid-coated peanuts, and then air-drying them to obtain coated peanuts; S3, the coated peanuts are first dried at 100°C for 1 min, and then dried at 65°C for 30 min using infrared rays to obtain dry peanuts; S4. The dried peanut kernels are pressed at a temperature of 50°C and a pressure of 40 MPa for 1 h, then at a temperature of 55°C and a pressure of 50 MPa for 1.5 h, and finally filtered at a temperature of 45°C to obtain finished peanut oil.
[0038] Embodiment 4: This embodiment differs from Embodiment 1 in that: During the preparation of the starch composite solution, no calcium caseinate was added to the starch gelatinized solution.
[0039] Embodiment 5: This embodiment differs from Embodiment 1 in that: During the preparation of the starch composite solution, there was no tetrapod-like zinc oxide whisker and sodium carboxymethyl cellulose solution on the surface of the hydroxyapatite nanowire filaments.
[0040] Embodiment 6: This embodiment differs from Embodiment 1 in that: During the preparation of the starch composite solution, no PMMA microspheres were added to the high acyl gellan gum solution.
[0041] Embodiment 7: This embodiment differs from Embodiment 1 in that: During the preparation of the starch composite solution, high acyl gellan gum solution and hydroxyapatite nanowires were not added.
[0042] Embodiment 8: This embodiment differs from Embodiment 1 in that: S2. Soak 10 kg of peanuts in 50 kg of starch composite liquid for 1 min, then remove the peanuts and drain off excess liquid on the surface to obtain liquid-coated peanuts. The liquid-coated peanuts are air-dried to obtain coated peanuts.
[0043] Comparative Example Comparative Example 1: The difference between this comparative example and Example 1 is that: S3. The coated peanuts are first dried at 130° C. for 35 min to obtain dry peanuts.
[0044] Comparative Example 2: The difference between this comparative example and Example 1 is that: S4. The dried peanut kernels are pressed at a temperature of 130°C and a pressure of 20 MPa for 3 h, and finally filtered at 80°C to obtain finished peanut oil.
[0045] Comparative Example 3: The difference between this comparative example and Example 1 is that: S2, drying the peanuts at 90° C. for 2 min, and then drying them at 60° C. for 35 min using infrared rays to obtain dry peanuts; S3. The dry peanut kernels are pressed at a temperature of 48°C and a pressure of 38 MPa for 1.2 h, then pressed at 52°C and a pressure of 48 MPa for 2 h, and finally filtered at a low temperature at 45°C to obtain finished peanut oil.
[0046] Performance testing 1. Oleic acid content detection Peanut oil was prepared by the preparation methods of Examples 1-7 and Example 3, respectively. The oleic acid content in the peanut oil was detected with reference to GB5009.168-2016. The oleic acid was calculated relative to the total fatty acid content, and the data was recorded.
[0047] 2. Oil yield detection Peanut oil was prepared by the preparation methods of Examples 1-8 and Ratios 1-3, respectively. The oil yield was calculated based on 100 kg of peanut kernels. The oil yield = (mass of peanut oil) / (mass of peanuts) × 100%.
[0048] 3. Acid value detection Peanut oil was prepared by the preparation methods of Examples 1-3, 6, 8 and Ratio 1-3, respectively. The acid value (in KOH) of the peanut oil was tested with reference to GB / T5530-2005 Determination of acid value and acidity of animal and vegetable oils and fats, and the data was recorded.
[0049] 4. Peroxide value detection Peanut oil was prepared by the preparation methods of Examples 1-3, 6, 8 and Ratio 1-3, respectively. The peroxide value of the peanut oil was tested with reference to GB / T5538-2005 Determination of Peroxide Value of Animal and Plant Oils and Fats, and the data was recorded.
[0050] 5. Color detection Peanut oil was prepared by the preparation methods of Examples 1-3 respectively, and the color grades were observed and recorded; grade 1, clear and transparent, light yellow; grade 2, light yellow with a little precipitation; grade 3, dark yellow with precipitation.
[0051] Table 1 Performance test table (“ / ” in the table means that the corresponding embodiment or comparative example did not test the item, so there is no data) It can be seen from Examples 1-3 and Table 1 that the peanut oil prepared in the present application has a higher oil yield and a higher oleic acid content, is not prone to oleic acid oxidation and thermal decomposition during the pressing process, and ensures the oleic acid content and quality of the peanut oil.
[0052] Combining Example 1 and Examples 4-9 and Table 1, it can be seen that in the preparation process of the starch composite liquid in Example 4, calcium caseinate was not added to the starch gelatinized liquid. Compared with Example 1, the oleic acid content and oil yield of the peanut oil prepared in Example 4 were lower than those in Example 1; this indicates that the starch, calcium caseinate and high acyl gellan gum solution are cross-linked to form a network structure with good toughness, which is convenient for providing a flow path for the oil to flow out during the oil pressing process, ensuring that the oil in the peanuts is efficiently extracted, so that the peanut oil has a higher oil yield and a higher oleic acid content.
[0053] During the preparation of the starch composite liquid in Example 5, there are no tetrapod-shaped zinc oxide whiskers and sodium carboxymethyl cellulose solution on the surface of the hydroxyapatite nanowire filaments. Compared with Example 1, the oleic acid content and oil yield of the peanut oil prepared in Example 5 are both lower than those in Example 1; this indicates that the tetrapod-shaped zinc oxide whiskers and sodium carboxymethyl cellulose solution cooperate with each other, and the carboxyl groups in sodium carboxymethyl cellulose cooperate with the hydroxyl groups in starch, and the carboxyl groups and hydroxyl groups in high acyl gellan gum are cross-linked and bonded to form an interwoven and folded network structure, which, together with the supporting effect of the tetrapod-shaped whiskers, further provides space for the circulation of oil in the oil pressing process, and the tetrapod-shaped zinc oxide whiskers in contact with the surface of the peanut kernels can penetrate into the interior of the peanut kernels during the pressing process, further promoting the pressing of the oil, thereby increasing the oil yield and the oleic acid content.
[0054] During the preparation of the starch composite liquid in Example 6, PMMA microspheres were not added to the high acyl gellan gum solution. Compared with Example 1, the peanut oil prepared in Example 6 had a lower oil yield and oleic acid content than those in Example 1, and a higher acid value and peroxide value than those in Example 1. This indicates that the presence of PMMA microspheres, by utilizing their infrared transmission effect, can promote infrared-ray-uniform drying of peanut grains. If the drying is not uniform, some peanut grains will have a high moisture content, which can easily affect the peanut oil yield and quality. In addition, the presence of PMMA microspheres can reduce the contact area between the external environment and oleic acid in peanuts, thereby ensuring the peanut oil yield and oleic acid content, and ensuring that the peanuts are not easily oxidized during the oil extraction process.
[0055] During the preparation of the starch composite liquid in Example 7, high acyl gellan gum solution and hydroxyapatite nanowires were not added. Compared with Example 1, the oleic acid and oil yield of the peanut oil prepared in Example 7 were lower than those in Example 1. This indicates that the high acyl gellan gum solution and hydroxyapatite nanowires cooperate to form a flexible network structure on the surface of the peanut grains. During the oil extraction process, it can not only block the contact between external oxygen and oleic acid in the peanuts, but also prevent adjacent peanuts from sticking together due to oil and blocking the oil outflow path. Therefore, the gaps in the network structure are used to ensure the outflow of oil, thereby achieving efficient extraction of peanut oil, so that the peanut oil has the advantages of high oleic acid and high oil yield.
[0056] The liquid-coated peanuts in Example 8 were not treated with vitamin E. Compared with Example 1, the peanut oil prepared in Example 8 had a lower oil yield than that in Example 1, and a higher acid value and peroxide value than that in Example 1. This indicates that vitamin E can block external oxygen from oxidizing oleic acid in peanuts during the oil pressing process. During the oil pressing process, the fat-soluble vitamin E is gradually extracted along with the peanut oil, ensuring that the peanut oil has a good antioxidant effect.
[0057] Combining Example 1 and Comparative Examples 1-3 and Table 1, it can be seen that in Comparative Example 1, the coated peanut grains were first dried at 130° C. for 35 minutes to prepare dry peanut grains, compared with Example 1; the peanut oil prepared in Comparative Example 1 had an acid value and a peroxide value greater than that in Example 1, indicating that high-temperature drying easily leads to oxidation and thermal decomposition of oleic acid, thereby affecting the oleic acid content in the peanut oil.
[0058] In Comparative Example 2, dry peanut kernels were pressed at high temperature to prepare peanut oil, compared with Example 1; the peanut oil prepared in Comparative Example 2 had a higher acid value and peroxide value than that in Example 1, indicating that high-temperature pressing easily leads to oxidation and thermal decomposition of oleic acid, thereby affecting the oleic acid content in the peanut oil.
[0059] The surface of the peanut kernels in Comparative Example 3 was not treated with the starch composite liquid. Compared with Example 1, the peanut oil prepared in Comparative Example 3 had lower oleic acid and oil yield than Example 1, and higher acid value and peroxide value than Example 1. This indicated that the starch composite liquid treatment formed an interwoven and folded network structure on the surface of the peanut kernels, which could not only block the contact of external oxygen with the peanuts and control the oxidation of oleic acid in the peanuts, but also ensure the oil yield during the oil pressing process. At the same time, the squeezed peanut oil had better antioxidant effect, so that the finished peanut oil had the advantages of high oleic acid, high oil yield and high quality.
[0060] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing high oleic peanut oil with original flavor, characterized in that: The steps include: S1. Peanuts are selected, mold is removed, and red skin is removed to obtain peanut kernels; S2, soaking the peanuts in the starch composite liquid for 1-2 minutes, then taking out the peanuts and draining off the excess liquid on the surface to obtain liquid-coated peanuts, and drying and post-treating the liquid-coated peanuts to obtain coated peanuts; S3, the coated peanuts are first dried at 80-100°C for 1-3 minutes, and then irradiated and dried with infrared rays at 60-65°C for 30-40 minutes to obtain dry peanuts; S4. The dried peanut kernels are pressed and filtered at low temperature to obtain finished peanut oil.
2. The method for preparing high oleic peanut oil with original flavor according to claim 1, characterized in that: The starch composite liquid is prepared from starch gelatinized liquid, hydroxyapatite nanowires, high acyl gellan gum solution and glycerol in a mass ratio of 100:1-2:20-30:2-6.
3. The method for preparing high oleic peanut oil with original flavor according to claim 2, characterized in that: The starch gelatinized liquid is prepared by the following method: Weigh starch, add water and stir evenly, then heat and gelatinize to obtain starch liquid; add calcium caseinate to the starch liquid at a mass ratio of 1:0.05-0.1, mix and stir evenly to obtain starch gelatinized liquid.
4. The method for preparing high oleic peanut oil with original flavor according to claim 2, characterized in that: The hydroxyapatite nanowires are prepared by the following method: A sodium carboxymethyl cellulose solution is evenly sprayed on the hydroxyapatite nanowire filaments at a mass ratio of 1:0.1-0.2, and then tetrapod-shaped zinc oxide whiskers are added, the mass ratio of the hydroxyapatite nanowire filaments to the tetrapod-shaped zinc oxide whiskers is 1:0.1-0.3, and the finished product is obtained after drying and dispersion.
5. The method for preparing high oleic peanut oil with original flavor according to claim 4, characterized in that: The average length of the hydroxyapatite nanowire filaments is 200-600 μm.
6. The method for preparing high oleic peanut oil with original flavor according to claim 2, characterized in that: The high acyl gellan gum solution is prepared by the following method: Weigh high acyl gellan gum, place it in water and stir, heat it to 85-90° C. and stir until it is completely dissolved to obtain a dissolving solution, then mix the dissolving solution and PMMA microspheres at a mass ratio of 100:1-5 to obtain a finished product.
7. The method for preparing high oleic peanut oil with original flavor according to claim 1, characterized in that: The specific steps of the post-processing are as follows: Spray vitamin E evenly on the surface of the liquid-coated peanuts at a mass ratio of 100:1-2, and then air-dry.
8. The method for preparing high oleic peanut oil with original flavor according to claim 1, characterized in that: The selection is to select peanuts whose oleic acid content accounts for 75-80% of the total fatty acid content.
9. The method for preparing high oleic peanut oil with original flavor according to claim 1, characterized in that: The specific steps of low temperature pressing are as follows: First, press at a temperature of 45-50°C and a pressure of 35-40MPa for 1-1.5h; then press at a temperature of 50-55°C and a pressure of 45-50MPa for 1.5-2.5h.
10. The method for preparing high oleic peanut oil with original flavor according to claim 1, characterized in that: The temperature of the low temperature filtration is 40-45°C.
Citation Information
Cited By
Method for extracting high-oleic-acid peanut oil with original flavor
CN120290251A
A method for extracting a raw flavor high oleic peanut oil
CN120290251B
